Morphological and Structural Studies on Cu(II) Substituted Vanadium Heteropolyoxometalate Thin Films - R. PATIL, VANDANA; BHOSALE, P.N. (Asian Journal of Chemistry, 2010)
Copper(II) substituted vanadium heteropolyoxometalate thin films were deposited on glass substrates by simple chemical bath deposition technique. The thin films were characterized for their structural, morphological, compositional and optoelectronic, properties using XRD, SEMEDAX data, UV-visible spectra, TGA-DTA, electrical resistivity. X-ray diffraction study confirmed that the films are nanocrystalline in nature having cubic spinel structure. UV-visible spectroscopy revealed that, direct band to band transition with 2.6 ev band gap. The d.c electrical resistivity was measured in the temperature range of 27-270 °C, shows negative resistance region in the temperature range of 120 to 250 °C indicating semiconducting nature of heteropolyoxometalate material. Compositional analysis (EDAX) of samples shows the Cu(II) is intercalated in phosphovanadate anion. The TGA-DTA data revealed that the vanadium heteropolyoxometalate sample is thermally stable upto 250 °C.